Oral Administration of Probiotics Reduces Chemotherapy-Induced Diarrhea and Oral Mucositis: A Systematic Review and Meta-Analysis - Feng, Jing; Gao, Min; Zhao, Chengcheng; Yang, Jian; Gao, Haiyan; Lu, Xin; Ju, Rong; Zhang, Xiuwei; Zhang, Yunlei (Frontiers in Nutrition, 2022)
Background: Chemotherapy generally causes serious diarrhea and oral mucositis in cancer patients, and subsequently affects treatment. Oral administration of probiotics provides a therapeutic choice to address these limitations. This study aims to conduct a systematic review and meta-analysis on the efficacy of oral probiotic use in the management of the chemotherapy-induced adverse reactions, and to summarize the mechanisms underlying the action. Methods: We searched PubMed, Embase, ClinicalTrials.gov, and Web of Science from the start of the study to its completion on Dec. 31, 2021. Risk of bias was assessed using Cochrane Collaboration's Tool. Statistical analysis of the acquired data was performed via the RevMan and the Stata Statistical Software. The protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO registration number: CRD42020220650). Results: Twelve randomized controlled trials including 1013 patients were recruited and analyzed via the standard procedure of meta-analysis. In contrast to the control group, orally taking probiotics significantly decreased the risk of chemotherapy-induced diarrhea (≥ 1 grade) (RR = 0.70; 95% Cl: 0.56, 0.88; P = 0.002) and oral mucositis (≥ 1 grade) (RR: 0.84; 95% Cl: 0.78, 0.91; P < 0.00001) at all grades. Further analysis found that severe diarrhea (≥ 2 grades) (RR: 0.50; 95% Cl: 0.32, 0.78; P = 0.002) and severe oral mucositis also significantly declined (≥ 3 grades) (RR: 0.66; 95% Cl: 0.55, 0.79; P < 0.00001) after oral probiotic use. Interestingly, the beneficial effects of probiotics displayed statistically significant only in Asian patients. Importantly, the more species of bacteria they took, the lower the incidences of the adverse reactions occurred. We used Egger’s test P value to confirm that there is no publication bias. Conclusions: This meta-analysis demonstrated that orally administrated probiotics has a potential to decrease chemotherapy-induced diarrhea and oral mucositis incidences. However, the efficacy of oral probiotic use against the adverse reactions needs to be further verified through more clinical trials, and the species and number of probiotics have to be optimized and standardized prior to clinical applications.